Potential of lactic acid bacteria as probiotic from Malaysian stingless bee's gut / Nurul Ammar Illani Jaafar - Jaafar, Nurul Ammar Illani (2017)
Two hundred and twenty six lactic acid bacteria (LAB) were isolated from the gut of four species of Malaysian stingless bee Heterotrigona itama, Geniotrigona thoracica, Tetragonula laeviceps and Tetrigona Melanoleuca in order to identify the potential probiotic strains. These isolates fit the classification of lactic acid bacteria as Gram-positive bacteria, catalase negative and oxidase negative. Among all the LAB isolates, there are 7 isolates exhibited as potential probiotic with high antimicrobial properties, tolerance to acid pH 2.5, simulated gastric juice and 0.3% bile salt conditions after incubation within 3 hours which are the key criteria in potential probiotic selection. Those 7 LAB isolates are name as TIS 5, TIS 25, TID 18, TTD 6, TLBL13, TLH 16 and TMH 2. The 7 LAB isolates exhibited high antimicrobial activity against Staphylococcus aureus ATCC 25923, Eschericia coli ATCC 11775, Pseudomonas aeruginosa ATCC 27853 and Salmonella typhimurium ATCC 14028. Isolate TID 18 is significantly had high inhibition against the pathogenic bacteria compare to other isolated LAB. Isolate TID 18 demonstrated significantly high percentage tolerance to acid and simulated gastric juice while TIS 5 demonstrated high tolerance to bile salt. As for antibiotic resistance, all LAB isolates are less susceptible to antibiotic streptomycin, gentamycin, tetracycline, kanamycin and ampicillin except for isolates TIS 5 and TIS 25 which were inhibit by ampicillin. Interestingly, all LAB isolates also be able to grow in condition of medium supplemented 0.2% and 0.5% phenol. Isolates TID 18 and TTD 6 were found significantly have high ability to adhere to solvents such as n-hexane, chloroform and ethyl acetate. All LAB isolates also had high aggregation ability which related to cell adherence properties within 3 hours exposing to PBS solution.